2023
DOI: 10.1186/s13018-023-03955-7
|View full text |Cite
|
Sign up to set email alerts
|

CircZNF367 promotes osteoclast differentiation and osteoporosis by interacting with FUS to maintain CRY2 mRNA stability

Abstract: Background Osteoporosis, characterized by reduced bone mass and deterioration of bone quality, is a significant health concern for postmenopausal women. Considering that the specific role of circRNAs in osteoporosis and osteoclast differentiation remains poorly understood, this study aims to shed light on their involvement in these processes to enhance our understanding and potentially contribute to improved treatment strategies for osteoporosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Standardizing the diagnosis of ONJ might be possible by a valuable biomarker, which could be also used to evaluate the risk in patients undergoing bisphosphonates treat-ment [52][53][54][55]. Numerous studies have hypothesized that circRNAs may sequester miRNAs to modify mRNA expression [56] and some of them, via their effects on ONJ-related miR-NAs, are essential in RANKL-induced RAW264.7 cells treated with bisphosphonates [57] (Figure 2).…”
Section: Circularrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardizing the diagnosis of ONJ might be possible by a valuable biomarker, which could be also used to evaluate the risk in patients undergoing bisphosphonates treat-ment [52][53][54][55]. Numerous studies have hypothesized that circRNAs may sequester miRNAs to modify mRNA expression [56] and some of them, via their effects on ONJ-related miR-NAs, are essential in RANKL-induced RAW264.7 cells treated with bisphosphonates [57] (Figure 2).…”
Section: Circularrnasmentioning
confidence: 99%
“…Standardizing the diagnosis of ONJ might be possible by a valuable biomarker, which could be also used to evaluate the risk in patients undergoing bisphosphonates treatment [52][53][54][55]. Numerous studies have hypothesized that circRNAs may sequester miRNAs to modify mRNA expression [56] and some of them, via their effects on ONJ-related miRNAs, are essential in RANKL-induced RAW264.7 cells treated with bisphosphonates [57] (Figure 2). Patients with ONJ showed higher blood levels of miR-23a and lower serum levels of miR-145: miR-23a targets specific genes such as osteoclast stimulating factor 1 (OSTF1), secreted protein acidic and rich in cysteine (SPARC) and SPOCK1, low-density lipoprotein receptor-related protein 5 (LRP5), while miR-145 acts on interleukin (IL) and genes related to bone homeostasis, such as osteomodulin, and secreted protein acidic and rich in cysteine.…”
Section: Circularrnasmentioning
confidence: 99%
“…Thus, by regulating key signaling pathways involved in this process, circRNAs have been implicated in modulating osteoclastogenesis. For instance, Deng et al reported that CircZNF367 promotes osteoclasogenesis and can contribute to osteoporosis through the interaction with FUS, maintaining the stability of CRY2 mRNA and thus enhancing proliferation and TRAP, NFATc1, and c-FOS expression in osteoclast [ 70 ]. Tang et al have demonstrated that circ_0029463 drives osteoclast differentiation through the modulation of the miR-134-5p/Rab27a axis and promoting RANKL-induced differentiation [ 10 ].…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 99%
“…Profiling studies have identified distinct circRNA expression patterns in pathological bone tissues compared to healthy controls, offering insights into disease mechanisms and potential therapeutic targets [ 22 ]. Indeed, dysregulation of most of the aforementioned circRNAs associated with osteogenesis or osteoclastogenesis is involved in the pathogenesis of skeletal diseases [ 9 , 55 , 56 , 67 , 68 , 70 ]. However, research in recent years has significantly increased the number of identified circRNAs associated with skeletal pathologies and many other circRNA molecules are continually being discovered.…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 99%